Evaluation of presepsin as a diagnostic tool in newborns with risk of early-onset neonatal sepsis - Iva Pospisilova; Iva Pospisilova; Helena L. Brodska; Marketa Bloomfield; Marketa Bloomfield; Klara Borecka; Jan Janota; Jan Janota; Jan Janota (Frontiers Media S.A., 2023)
ObjectivesTo evaluate the efficacy of presepsin (P-SEP) as a potential biomarker of early-onset neonatal sepsis (EOS) and compare it to other routinely used markers of inflammation. To establish the cut-off values of P-SEP for EOS.Study design184 newborns were prospectively recruited between January 2018 to December 2020. Newborns >34th gestational week with suspected infection were included up to 72 h after delivery, and divided into three categories (i.e., unlikely, possible, and probable infection) based on risk factors, clinical symptoms and laboratory results. Values of plasma P-SEP were sequentially analyzed.ResultsMedian values of P-SEP in newborns with probable infection were significantly higher compared to healthy newborns (p = 0.0000013) and unlikely infection group (p = 0.0000025). The AUC for discriminating the probable infection group from the unlikely infection group was 0.845 (95% Cl: 0.708-0.921). The diagnostic efficacy of P-SEP was highest when used in combination with IL-6 and CRP (0.97; 95% CI: 0.911-0.990). The optimal cut-off value of P-SEP was determined to be 695 ng/L.ConclusionP-SEP, when combined with IL-6 and CRP, may be utilized as a negative predictive marker of EOS (NPV 97.2%, 95% CI: 93.3-101), especially in newborns at low to medium risk of infection.